EFFECTIVENESS OF CORRECTION OF POSTPARTUM LUMBOPELVIC PAIN IN WOMEN WITH PELVIC FLOOR DYSFUNCTION AFTER VARIOUS METHODS OF DELIVERY USING PHYSICAL THERAPY - Churpii-Dydyrko, I. I. (Rehabilitation and Recreation, 2025)
Aim – to evaluate the effectiveness of the developed comprehensive physical therapy program for women with pelvic floor dysfunction after vaginal and abdominal delivery according to indicators associated with lumbopelvic pain. Material. 175 women participated in the study. The control group consisted of 32 women who had no history of pregnancies and were not characterized by diagnosed pelvic floor dysfunction. The group with signs of pelvic floor dysfunction in the postpartum period consisted of 143 women who were divided into two groups (comparison – gave birth vaginally and main – gave birth abdominally) with two subgroups in each. Subgroup 1 was restored according to the recommendations of clinical protocols, subgroup 2 – according to the developed physical therapy program lasting 3 months with the use of therapeutic exercises (for the lower extremities, pelvic girdle, trunk, with a wireless Kegel trainer), preformed physical factors (pelvic floor muscle stimulator), educational component. The effectiveness was assessed by the results of the visual analogue pain scale, Oswestry Disability Index, Pelvic Girdle Questionnaire, Pregnancy Mobility Index, Ott, Schober, Thomayer, Sedin tests, and the deadlift index. Results. Women with pelvic floor dysfunction after childbirth, regardless of abdominal or vaginal delivery, remain at high risk of new and prolongation of existing signs of lumbopelvic pain. Lumbopelvic pain in them in the late postpartum period is associated with moderate pain (according to the visual analog scale), limitations in vital activity (according to the Oswestry Disability Index, Pelvic Girdle Questionnaire, Pregnancy Mobility Index), deterioration of spinal mobility even in the absence of pain syndrome (determined by the Ott, Schober, Thomayer, Sedin tests), decreased back muscle strength (according to the deadlift index). The use of a physical therapy program with the use of specific methods of influence aimed at leveling pelvic floor dysfunction in combination with a set of therapeutic exercises for the trunk and extremities allowed a statistically significant (p<0.05) improvement in the results of the visual analogue scale, Oswestry Disability Index, Pelvic Girdle Questionnaire, Pregnancy Mobility Index, and deadlift index over three months in comparison with the baseline parameters and the corresponding indicators of women who recovered independently. The magnitude of the absolute achieved effect of the physical therapy program depended on the initial parameters associated with the type of childbirth – abdominal or vaginal, but was proportionally the same for both methods of childbirth. Conclusions. Physical therapy is advisable to prescribe to reduce the intensity of symptoms of lumbopelvic pain and prevent the chronicity of pain syndrome in women with postpartum pelvic floor dysfunction, which threatens with psychoneurological disorders, loss of work capacity, and decreased quality of life, i.e. for faster postpartum recovery of women and their return to full-fledged life activities.